Pseudomonas sp. strain Neni-12 Growth on Acrylamide Exhibit Substrate Inhibition (Bulletin of Environmental Science and Sustainable Management (e-ISSN 2716-5353), 2023)
The bacterium Pseudomonas sp. strain Neni-12 isolated from volcanic soil showed the ability to grow on high concentrations of acrylamide. The acrylamide-degrading bacterium grew best in the presence of glucose with acrylamide as the sole nitrogen source. The inhibitory effects of acrylamide as a substrate for growth of this bacterium on the growth rate was modelled using several secondary models such as Haldane, Monod, Moser, Webb, Teissier (Tessier), Han-Levenspiel, Yano-Koga, Aiba, Luong, Webb and Hinshelwood. The models Luong and Han-Levenspiel failed to fit the data. The statistical analysis and accuracy of the all six kinetic models used indicated that Haldane was the best model with small values for RMSE and AICc, adjusted R2 values, F-test and with Bias Factor and Accuracy Factor nearest to unity (1.0). The Haldane’s constants: maximal growth rate, half-saturation constant for maximal growth and half-inhibition constant symbolized by max, Ks, and n were 1.637 h-1 (95% C.I., 1.297 to 1.978), 210.99 mg/L (95% C.I., 135.01 to 286.97), 5198 mg/L (95% C.I., 4642 to 5755) and 545.68 (95% C.I., 389.94 to 701.43), respectively. The model’s parameter obtained in this study will be very useful in future scale-up macrocosm studies.
Keywords: Acrylamide-degrading; Pseudomonas sp.; Bioremediation; Haldane; Haldane Substrate inhibition kinetics